2011
DOI: 10.1111/j.1365-2036.2011.04634.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: the efficacy of anti-viral therapy in prevention of recurrence after curative treatment of chronic hepatitis B-related hepatocellular carcinoma

Abstract: SUMMARY BackgroundThe role of anti-viral therapy in prevention of hepatocellular carcinoma (HCC) recurrence is to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 33 publications
(74 reference statements)
9
131
3
2
Order By: Relevance
“…It has been reported that nucleoside/nucleotide analogs (NA) in hepatitis Brelated HCC (B-HCC) and interferon (IFN)-based therapy in hepatitis C-related HCC (C-HCC) had beneficial effects in terms of preventing recurrence and preserving liver function. [12][13][14] However, these trials enrolled only selected patients with specific conditions. It is not well documented whether the prognosis outside of clinical trials actually improved following radical percutaneous therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nucleoside/nucleotide analogs (NA) in hepatitis Brelated HCC (B-HCC) and interferon (IFN)-based therapy in hepatitis C-related HCC (C-HCC) had beneficial effects in terms of preventing recurrence and preserving liver function. [12][13][14] However, these trials enrolled only selected patients with specific conditions. It is not well documented whether the prognosis outside of clinical trials actually improved following radical percutaneous therapy.…”
Section: Introductionmentioning
confidence: 99%
“…El beneficio de terapia neoadyuvante o adyuvante se ha estudiado en múltiples trabajos sin que por el momento se encontraran evidencias que justifiquen su uso estandarizado, aunque algunos tratamientos antivirales podrían ofrecer beneficios 40 .…”
Section: Resección Hepáticaunclassified
“…Meta-analysis of these studies have concluded that NA therapy is associated with significantly lower tumor recurrence and liver-related mortality and significantly higher OS in patients with HBV-related HCC than no adjuvant therapy after curative treatments [20,21]. Unfortunately, the retrospective design of these studies limits the strength of their evidence.…”
mentioning
confidence: 98%